BioInfoWF – WEB SERVICES AND WEB INTERFACES GENERATOR FOR BIOINFORMATICS ANALYSIS - M. A. Genaev; E. G. Komyshev; K. V. Gunbin; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
The BioinfoWF (Bioinformatics WorkFlow) system for automated generation of Web interface and Web services for bioinformatics programs. Each program module used in the system has metadescription in XML. The metadescriptions are used for automated generation of Web interface and Web services that can be used further in bioinformatics workflows. Computational modules can be organized in workflows. The tool we have developed significantly simplify the design and publication of modules for bioinformatics data analysis via the internet and their availability for scientific communities. The developed system makes is distributed under GNU GPL. The Source codes and documentation for BioinfoWF are available at http://bioinfowf.bionet.nsc.ru.